Infrastructural semantics: postal networks and statistical accounts in Scotland, 1790–1845. Issue 12 (2nd December 2019) - Gidal, Eric; Gavin, Michael
ABSTRACT: Our research combines GIS with computational semantics and network analysis to explore historical connections between language and infrastructure. Our focus is Scotland in the nineteenth century, a cultural region and economic zone that experienced rapid industrialisation as a crucial hub of British manufacturing and transport. We have built a network model from the collection of postal directories published online by the National Library of Scotland and have combined it with the parish reports collected into the 'Old' and 'New' Statistical Accounts of Scotland in the 1790s and 1830–40s respectively. The postal directories provide the names and addresses of local businesspeople and tradesmen, as well as mail coach routes and times, postal delivery dates, carrier schedules, canal and rail departures, and shipping calendars. The Statistical Accounts provide regional representations of national transport and communication, alongside records of population growth and agricultural development, ecclesiastical history and local antiquities, manufacturing, resource extraction, and energy consumption. When combined, these datasets allow us to compare changing patterns in geographic description with transformations in the infrastructural networks that supported Scotland's industrial development.